Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1556/018.69.2018.4.10
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical changes in ears of wheat genotypes subjected to Fusarium spp. attack

Abstract: In wheat, Fusarium fungus promotes the appearance of destructive disease named as Fusarium head blight (FHB) that can cause grain yield reduction and mycotoxin accumulation. The focus of this research was to verify the influence of Fusarium graminearum and F. culmorum on wheat genotypes with different susceptibility to FHB: "Super Žitarka" (susceptible), "Lucija" (moderately resistant) and "Apache" (resistant). The experiment was performed under field conditions by artificial spore inoculation of ears at the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 40 publications
1
3
0
Order By: Relevance
“…In inoculated ears of 'Apache', a PHE increase accompanied with no changes in activities of antioxidant enzymes and a decrease in PPO activity, suggests that defence response in 'Apache' is based on PHE metabolism rather than ROS scavenging anti-oxidative enzymes. This statement is in accordance with Marcek et al (2018). On the contrary, stability of phenols and PPO in inoculated ears of 'U1' implied that PHE metabolism was not involved in its resistance.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…In inoculated ears of 'Apache', a PHE increase accompanied with no changes in activities of antioxidant enzymes and a decrease in PPO activity, suggests that defence response in 'Apache' is based on PHE metabolism rather than ROS scavenging anti-oxidative enzymes. This statement is in accordance with Marcek et al (2018). On the contrary, stability of phenols and PPO in inoculated ears of 'U1' implied that PHE metabolism was not involved in its resistance.…”
Section: Discussionsupporting
confidence: 82%
“…The significant decrease in H2O2 content occurred at 1 hai in 'Apache' and 'U1', as well as at 2 hai in 'Apache' inoculated by Fusarium in comparison to naturally infected plants. Marcek et al (2018) found that rapid overproduction of H2O2 under Fusarium infection caused stress started 3 h after Fusarium exposure. It suggests that decreased content of H2O2 at 1 and 2 hai in current investigation was consequence of signalling role of H2O2 rather than its ROS role (Ge et al 2013).…”
Section: Discussionmentioning
confidence: 98%
“…Both SOD and CAT activities in the single mycotoxin exposure groups were not markedly altered, indicating that the determined concentration of single mycotoxin was insufficient to induce prominent oxidative stress. However, a prominent reduction was found in the high-concentration group of JOT in comparison to the corresponding single-exposure group of DON, which could be attributed to an overwhelmed antioxidant capacity [43]. MDA is the primary by-product of LPO, and an elevation in its content incarnates the degree of the cell damage caused by free radicals [44].…”
Section: Discussionmentioning
confidence: 95%
“…Both SOD and CAT activities in the single mycotoxin exposure groups were not markedly altered, indicating that the determined concentration of single mycotoxin was insu cient to induce prominent oxidative stress. However, a prominent reduction was found in the high-concentration group of JOT in comparison to the corresponding single exposure group of DON, which could be attributed to an overwhelmed antioxidant capacity [43]. LPO is a reliable oxidative stress indicator since it plays a critical role in denoting cell damage.…”
Section: Discussionmentioning
confidence: 98%